Part II: presentation, diagnosis, classification, treatment, and prevention of stress fractures in female athletes - Abbott, A.; Bird, M.; Brown, S. M.; Wild, E.; Stewart, G.; Mulcahey, M. K. (The Physician and Sportsmedicine, 2020)
Objectives: Stress fractures (SFx) occur as the result of repetitive loads over short periods of time, which leads to micro-damage of the bone through cortical resorption, ultimately leading to fracture. They are a common injury in female athletes and often cause significant morbidity. The goal of this study is to review the presentation, diagnosis, classification, treatment, and prevention of SFx in female athletes.